2014
DOI: 10.1063/1.4869035
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical deposition of iron sulfide thin films and heterojunction diodes with zinc oxide

Abstract: Structure and optoelectronic properties of spray deposited Mg doped p -CuCrO 2 semiconductor oxide thin films J. Appl. Phys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
3
16
0
1
Order By: Relevance
“…The spectra in Fig. 5 are not significantly different from that observed for iron sulfide deposited by the same technique, which has much reduced oxygen content [20], and therefore we are unable to confirm any widening of the band gap due to the substitution of sulfur with oxygen. Fig.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…The spectra in Fig. 5 are not significantly different from that observed for iron sulfide deposited by the same technique, which has much reduced oxygen content [20], and therefore we are unable to confirm any widening of the band gap due to the substitution of sulfur with oxygen. Fig.…”
Section: Resultsmentioning
confidence: 66%
“…Further, the fabrication of heterostructure devices based on FeS x O y has never been attempted. Recently, Kawai et al reported ECD of iron sulfide thin films and fabrication of pn heterojunction diodes based on ECD-iron sulfide [20]. In this work, we deposited FeS x O y thin films by ECD.…”
Section: Introductionmentioning
confidence: 92%
“…Dong et al [10] studied the effect of sulfurization temperature on the structure of Ferrous sulfide (FeS) thin films deposited on indium-tin oxide (ITO) substrates by electrochemical deposition, whilst Wang et al [11] studied the effect of sulfurization time on the structure of electrodeposited iron sulfide thin films. Finally, Kawai et al [12] studied the optimal conditions for the electrodeposition of iron sulfide thin films. Each of these authors used their own unique electrochemical factors such as pH, electrolyte concentration, deposition potential, and temperature and deposition time.…”
Section: Introductionmentioning
confidence: 99%
“…В большинстве случаев при исследовании электрических свойств наблюдают p-тип проводимости пирита. С использованием пленок p-FeS 2 изготавливают выпрямляющие ток гетероструктуры ZnO/p-FeS 2 [6] и создают омические контакты к p-CdTe в структурах n-CdS/p-CdTe/p-FeS 2 /Au [7]. При участии хлора в процес-сах выращивания пленок, который компенсирует дыроч-ный тип проводимости, получают n-FeS 2 [8].…”
Section: Introductionunclassified